Vulnerable groups in crisis situations: how to support roma students’ coping strategies - Varga Aranka (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. Crises occurring in each life-stage, are unavoidable conditions for personality development, as crisis is a natural part of human life. However, there are crises which are caused by unexpected life events, threatening or painful situations. Since the course of each crisis affects the individual's later life, the strategies used to cope with it are essential. Vulnerable groups are more exposed to situations leading to crisis, and they also need special attention and equitable support for a positive outcome. From among vulnerable groups, the presentation discusses Roma students in different life situations. Relying on research results, obstacles to their educational success are explored, and conditions leading to their resilient life paths are in the focus. The presentation covers extraordinary situations, such as war and the pandemic, presenting the difficulties that particularly affect Roma students. In addition, recent data are presented that numerically indicate that the phenomenon of early school leaving affects Roma students excessively. In the presentation, twenty-year long research will be covered, that accompanies Roma people into their adulthood, who grew up in segregated villages. Through their stories, we can learn about life situations full of obstacles and identify individual and social strategies that helped them resolve all these crises. Also, the result of a study examines successful coping mechanisms that aids individuals who deal with difficult situations and it points towards supporting factors of resilience. Analyzing the life path of Roma university students, the importance of psychological and social capital and the supportive power of an inclusive environment become transparent. Finally, the first results of an ongoing research and development are presented. Mentoring programs of ten small schools in Hungary are introduced, where teachers help Roma students from small villages to choose successful career paths. The program exemplifies how dedicated educators working with students in a mentoring role achieve the prevention of dropout among disadvantaged Roma students and the development of their ability to cope with difficulties. The study focuses on Roma pupils from vulnerable groups in different life situations. Two crisis situations – pandemic and war – especially highlight the increasing disadvantages. In addition, by looking at everyday situations, it explores the following questions, based on research findings; what are the barriers to school success for Roma pupils and what conditions lead to resilient life paths?
Sérülékeny csoportok és krízishelyzetek: a roma tanulók megküzdési lehetőségei
Keywords: roma students; vulnerable groups; crisis situations; coping strategies